Microwell bag culture for large-scale production of homogeneous islet-like clusters - Ryo Suenaga; Shuhei Konagaya; Junji Yamaura; Ryo Ito; Satoshi Tanaka; Yoichi Ishizaki; Taro Toyoda (Scientific Reports, 2022)
Abstract Pluripotent stem-cell derived cells can be used for type I diabetes treatment, but we require at least 105–106 islet-like clusters per patient. Although thousands of uniform cell clusters can be produced using a conventional microwell plate, numerous obstacles need to be overcome for its clinical use. In this study, we aimed to develop a novel bag culture method for the production of uniform cell clusters on a large scale (105–106 clusters). We prepared small-scale culture bags (< 105 clusters) with microwells at the bottom and optimized the conditions for producing uniform-sized clusters in the bag using undifferentiated induced pluripotent stem cells (iPSCs). Subsequently, we verified the suitability of the bag culture method using iPSC-derived pancreatic islet cells (iPICs) and successfully demonstrate the production of 6.5 × 105 uniform iPIC clusters using a large-scale bag. In addition, we simplified the pre- and post-process of the culture—a degassing process before cell seeding and a cluster harvesting process. In conclusion, compared with conventional methods, the cluster production method using bags exhibits improved scalability, sterility, and operability for both clinical and research use.